A bimodal probe for fluorescence and synchrotron X-ray fluorescence imaging of dopaminergic neurons in the brain. Issue 5 (4th January 2022) - Yan, Meiling; Zuo, Tingting; Zhang, Jichao; Wang, Yiyang; Zhu, Ying; Wang, Lihua; Zhou, Yi; Sun, Yanhong
Abstract : A bimodal probe, the erythrosine B (EB) conjugated immunoglobulin G complex (EB/IgG), has been developed for the fluorescence and synchrotron X-ray fluorescence (SXRF) imaging of dopaminergic neurons in the brain. Abstract : A bimodal probe, the erythrosine B (EB) conjugated immunoglobulin G complex (EB/IgG), has been developed for the fluorescence and synchrotron X-ray fluorescence (SXRF) imaging of dopaminergic neurons in the brain.